Konundrum : selected prose - Kafka, Franz
"In this new selection and translation, Peter Wortsman mines Franz Kafka's entire opus of short prose--including works published in the author's brief lifetime, stories published posthumously, journals, and letters--for narratives that sound the imaginative depths of the great German-Jewish scribe from Prague. It is the first volume in English to consider his deeply strange, resonantly humane letters and journal entries alongside his classic short fiction and lyrical vignettes. 'Transformed' is a vivid retranslation of one of Kafka's signature stories, 'Die Verwandlung,' commonly rendered in English as 'The Metamorphosis.' Composed of short, black-comic parables, fables, fairy tales, reflections, as well as classic stories like 'In the Penal Colony,' Kafka's uncanny foreshadowing of the Twentieth Century's nightmare, Konundrum refreshes the writer's mythic storytelling powers for a new generation of readers."--